Multimodal Discourse Analysis of Social Media Posts for Sports Festivals in Private Sector Colleges - Aqsa Areej; Muhammad Zahid; Dr. Muhammad Nadeem Anwar, (Dialogue Social Science Review (DSSR), 2025)
This study conducts a multimodal analysis of social media posts for sports festivals in private sector colleges, with a particular focus on the interplay between various modes of communication—visual, aural, linguistic, gestural, and spatial. Drawing on the framework proposed by Kress and van Leeuwen (1996), this research seeks to understand how these multimodal resources combine to construct meaning within sports event promotions. Adopting a qualitative, descriptive approach, data were collected from social media platforms, specifically Facebook and Instagram. The sample comprises four promotional posters: two sourced from Facebook and two from Instagram. Through this analysis, the study examines how visual, textual, and symbolic elements in banners and posters communicate key messages and evoke emotional engagement among the target audience. The findings confirm the importance of multimodal strategies in enhancing the appeal and promotional impact of sports festivals, highlighting the potential for well-crafted multimodal materials to generate excitement and participation.